Dampak Lingkaran (Circle) Pertemanan Terhadap Moral dan Karakteristik Mahasiswa - Astuti, Mardiah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research discusses the impact of friendship circles on the morals and characteristics of students. The article aims to examine how social interactions can influence one's attitudes, behaviors, and values. The goal is to help students understand the importance of choosing friends wisely because our social environment can greatly influence how we perceive the world and how we choose to interact with others. The method used in this research is qualitative, and the results indicate a deep understanding of social and human phenomena, such as in this context, how friendship circles affect the morals and characteristics of students. Qualitative research results are typically presented in the form of descriptive narratives based on data collected through interviews, observations, or document analysis. The research findings may indicate that students with friendship circles characterized by strong and positive values tend to exhibit better morals and characteristics. They are more likely to make ethical decisions, show empathy towards others, and behave consistently with moral principles. Additionally, the research may also suggest that friendship circles can serve as a crucial source of social support, assisting students in facing challenges and pressures in their daily lives and studies